Teachers’ Perspectives on Nepal’s Continuous Assessment System: Opportunities and Challenges - Bist, Nar Bahadur; Bohara, Nirajan (Exploration अन्वेषण, 2026)
Individual student success is influenced by the assessment system adopted by the teacher since continuous assessment, assessment for learning, provides feedback to the students for further improvement in regular classes. The study explored the opportunities offered by the CAS (Continuous Assessment System) and the challenges faced by teachers in implementing the continuous assessment system of grades one to three in Nepal, pursuing a qualitative method through a social constructivist lens. Four teachers practising the continuous assessment system in their schools were purposively selected as the research participants. The data were collected using semi-structured interviews and were analysed thematically. The findings show that a continuous assessment system offers an opportunity for students' learning improvement for weak students. Diverse abilities of students are assessed through CAS since it uses different tools of evaluation, not just a paper and pencil test and is extended beyond conventional methods. In addition, it develops the students' critical thinking skills. However, CAS has different implementation challenges, such as time-consuming, a lack of training, and difficulty in managing remedial teaching for weak students.